PENGOLAHAN LINDI (LEACHATE) DENGAN MODEL COAGULATION - BIOFILTER UNAEROBIC - Sri Puji Ganefati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Leachate, especially from the landfill, is a pollutant that can harm human health and pollute the environment including aquatic biota, because the leachate contains various chemicals both organic and inorganic substances and also pathogen bacteria. Laboratory test by Department of Health – Yogyakarta (2001) showed that leachate from landfill had Biological Oxygen Demand (BOD) of 1032 mg/liter in which this was much higher than the limit allowed (BOD = 150 mg/liter. In order to reduce BOD in leachate, a treatment is needed. In this experiment a treatment to reduce BOD in leachate was carried out by applying coagulation andanaerobic bio-filtration with the time of 1, 2, and 3 hours. Evaluation of the tests was conducted using pre-test and post-test with control design which analysis was made descriptive and analytically using T-test with the error of about 5% (á =0,05). Results of the experiment indicated that there was a tendency of BOD reduction of about 0.9% - 1.1% for the control samples, whereas the BOD reduction for leachate attained 82.3% -90.5%. Based on the T-Test, the probability result was 0.000 (p< á =0.05). This means that there is a significant difference in BOD reduction between control samples and leachate. In other words leachate treatment using coagulation – anaerobic bio-filtration can be taken as an alternative process to reduce BOD.